Scambio di informazioni tra amministrazioni finanziarie e tutela del contribuente - De Mattia, Elisa (Cultura giuridica e diritto vivente, 2014)
[Information exchange between financial administration and protection of taxpayer] The economic globalization and trade liberalization lead to the increase of tax evasion cases and tax fraud; taxpayers tend to take advantage of different tax systems’ peculiarities in order to obtain fiscal saving. For this reason, States can’t anymore act in complete autonomy, but they need cooperation instruments to be used between different administrations. This article intends to examine the discipline of information exchange in the Community context and at international level analyzing, on one hand, the 2011/16/EU Directive on administrative cooperation in the field of taxation between EU Member States (amendment of 77/799/CEE Directive) and, on the other, the article 26 of the OECD Model Tax Convention on double taxation regarding to information exchange. International cooperation can’t take account exclusively of States’ interests and of their institutional relationships, but it must also consider taxpayers’ interests and rights. In this regard, the article deals also with the analysis of the protection of taxpayer’s rights.